Bismuth Sulfide Nanorods as Efficient Photothermal Theragnosis Agents for Cancer Treatment - Jiang, Jing; Che, Xin; Qian, Yiwen; Wang, Luoziyi; Zhang, Yu; Wang, Zhiliang (Frontiers in Materials, 2020)
Bi2S3 nanostructures can theoretically have photothermal properties. However, there are few reports on the application of bismuth sulfide in photothermal therapy due to the poor photothermal effect. To address this problem, herein we obtained Bi2S3 nanorods with defect structures via a facile method. Due to the special shape and defects, the Bi2S3 nanorods exhibited a strong absorption band in the NIR region, thus showed excellent photothermal effect. The photothermal conversion efficiency of Bi2S3 nanorods was calculated to be as high as 78.1% due to the strong NIR absorption. Importantly, the photothermal ablation experiments both in vitro and in vivo proved that the Bi2S3 nanorods can effectively kill cancer cells under the irradiation of an 808 nm laser. In addition, Bi2S3 nanorods can be used as effective CT imaging agents due to inherently high X-ray attenuation coefficient of bismuth. Our work demonstrated that the Bi2S3 nanorods were very promising photothermal nanoplatforms for photothermal therapy of cancers, guided by CT imaging.